Penguasaan terhadap Visi, Misi dan Nilai-Nilai Organisasi serta Implikasinya terhadap Kinerja Individu: Diagnosis Organisasi Kelompok Restoran Pringsewu - Syafaruddin Alwi (Sinergi: Kajian Bisnis dan Manajemen, 2006)
This research is aim to investigate the understanding of managers of Pringsewu Group on vision, mission, and organizational values as well as implication on its business performance. This research would also highlight the role of structure, culture, as well as valuation and reward system on supporting business activities. Based on qualitative analysis, the result emphasize the importance both the understanding of managers of Pringsewu Group on vision, mission, and organizational values and the role of structure, culture, as well as valuation and reward system on supporting business activitiesKeywords: business performance, learning organization, organization pillar